Protective Effects of 17-βE2 on the Primary Hepatocytes of Rainbow Trout (Oncorhynchus mykiss) Under Acute Heat Stress - Guiyan Zhao; Zhe Liu; Junhao Lu; Jinqiang Quan; Yucai Pan (Antioxidants)
The rainbow trout (Oncorhynchus mykiss) is a typical cold-water species. However, due to global warming, it has experienced prolonged high-temperature stress. Research indicates that thermotolerance in rainbow trout varies by sex at multiple physiological levels. Specifically, females exhibit higher thermotolerance, which may be attributed to estrogen-mediated signal transduction pathways. This study involved culturing primary hepatocytes from rainbow trout and exposing them to estradiol and estrogen receptor antagonists to assess estradiol’s protective effects. The analysis focused on expression of ER, HSPs genes, hepatocyte viability, and antioxidant indices. Four experimental groups were treated with 17-βE2 at concentrations of 0, 0.1, 1, and 10 μM/mL for durations of 4, 8, 12, 24, and 48 h at 18 °C. 17-βE2 treatment led to increased hepatocyte viability and enhanced SOD, GSH-Px, and CAT levels but decreased MDA levels. hsp70a, hsp90β, era1, and erβ1 levels were notably higher, with the optimal 17-βE2 concentration being 1.0 μM/mL. Following heat stress (24 °C), the addition of 1.0 μM/mL 17-βE2 improved hepatocyte viability and increased SOD, GSH-Px, and CAT levels, while MDA content initially decreased before rising. The gene expression of hsp70a, hsp90β, era1, and erβ1 was significantly elevated compared to controls. Flow cytometry analysis showed increased apoptosis after heat exposure; however, 17-βE2 treatment significantly reduced the heat stress-induced effects (p < 0.05). In conclusion, 17-βE2 and mild heat stress collaboratively enhanced the expression of HSPs and estrogen receptors, thereby providing protection to hepatocytes from heat stress damage, indicating a beneficial protective role of estradiol in rainbow trout hepatocytes.